SCHEDULING ANALYSIS IN CONSTRUCTION WITH THE PERT METHOD USING MICROSOFT PROJECT - Prasetyo, Baskoro Adhi; Haris Muhammadun; Laksono Djoko Nugroho (International Journal Science and Technology, 2023)
Since 2017, the Drinking Water Supply System (SPAM) of the Capital District (IKK) Ibu has not been functioning due to damage to the pipe network due to road widening work, damage to generators and pumps, thus PDAM West Halmahera will build a new SPAM network system with a gravity system and will analyze scheduling using the Program Evaluation and Review Technique (PERT) method using Microsoft Project 2021 to carry out development planning which has results where the time required for construction is 320 days and can be completed with a percentage level of 95.35%, with a critical path found in the implementation work occupational health and safety, preparation, piping work, procurement and installation of house connections and commissioning test work with a time of 273 days.